Back to the Future? What the Politics of the Late Nineteenth Century Can Tell Us about the 2016 Election. Issue 1 (September 2016) - Azari, Julia; Hetherington, Marc J.
The politics and party system of the late Civil War era are strikingly similar to what we have in the present day. Elections were consistently close; race, culture, immigration, and populism were salient issues; and states almost always voted for the same party in election after election. The states that supported Democrats then, however, mostly support Republicans now, and vice versa. In 1896, though, a new party system began to emerge. In this article, we evaluate bygone elections alongside contemporary ones to assess whether 2016 might be the beginning of something new in American electoral politics. Are national politics likely to follow the familiar pattern of the last four presidential races, or are Americans going to be presented altogether different choices? Our analysis suggests that race and populism are guideposts for potential change in 2016: if the concerns of race continue to define political conflict, the electoral map should change little, but if economic populism eclipses race as it did in 1896, a new political era may be ushered in in America.